The Blackwell companion to the study of religion - Segal, Robert Alan (Blackwell companions to religion, 2006)
Anthropology of religion / Fiona Bowie -- The comparative method / Paul Roscoe -- Economics of religion / Rodney Stark -- Literature and religion / Stephen Prickett -- Phenomenology of religion / Thomas Ryba -- Philosophy of religion / Charles Taliaferro -- Psychology of religion / Roderick Main -- Sociology of religion / Grace Davie -- Theology / Ian Markham -- Body / Richard H. Roberts -- Death and afterlife / Douglas J. Davies -- Ethics / G. Scott Davis -- Fundamentalism / Henry Munson -- Heaven and hell / Jeffrey Burton Russell -- Holy men/holy women / Lawrence S. Cunningham -- Magic / Gustavo Benavides -- Modernity and postmodernity / Colin Campbell -- Mysticism / Jeffrey J. Kripal -- Myth / Robert A. Segal -- Nationalism and religion / Mark Juergensmeyer -- New religious movements / Lorne L. Dawson -- Pilgrimage / Simon Coleman -- Ritual / Catherine Bell -- Secularization / Steve Bruce